Effect of pioglitazone on inflammatory response and clinical outcome in T2DM patients with COVID-19: a randomized multicenter double-blind clinical trial - Baagar, Khaled; Alessa, Thamer; Abu-Farha, Mohamed; Abubaker, Jehad; Alhumaidi, Heba; Franco Ceruto, Jose Antonio; Hamad, Mohammad Khair; Omrani, Ali; Abdelrahman, Salma; Zaka-Ul Haq, Muhammad; Safi, Abdul Wajid; Alhariri, Bassem; et al. (Frontiers in Immunology, 2024)
Background: COVID-19 is caused by the coronavirus SARS-CoV-2, has emerged as a rapidly spreading contagious disease across the globe. Recent studies showed that people with diabetes mellitus, severe obesity, and cardiovascular disease are at higher risk of mortality from COVID-19. It has been suggested that the increased risk is due to the chronic inflammatory state associated with type 2 diabetes. This study aimed to evaluate the efficacy of pioglitazone, a strong insulin sensitizer with anti-inflammatory properties, in improving the clinical outcomes of patients with type 2 diabetes admitted with moderatesevere COVID-19.We enrolled 350 patients with type 2 diabetes who were admitted to hospitals in Qatar and Kuwait with COVID-19. Patients were randomized to receive in a double-blind fashion pioglitazone (n=189) or matching placebo (n=161) for 28 days. The study had two primary outcomes: (1) the incidence of a composite outcome comprised of (a) requirement for mechanical ventilation; (b) death, (c) myocardial damage; and (2) an increase in C-reactive protein (CRP) levels.The first primary outcome occurred in 28 participants (8%), and the secondary outcome occurred in 17. Treatment with pioglitazone showed a significant reduction in interleukin-3 (IL-3) levels compared with placebo treatment (Mean (SD) 2.73 (±2.14); 95% CI: 0.02, 1.1, p=0.043 vs 2.28 (±1.67); 95%CI: -0.23, 0.86, p=0.3, respectively) with no effect seen in the levels of other inflammatory markers. Even though not significant, few of the patients on pioglitazone exhibited serum Troponin levels >3 times higher than the normal range seen in patients on placebo. On the other hand, more patients on pioglitazone were admitted to the ICU than those with placebo, and no significant difference in the CRP reduction was observed between the two groups.The results of the present study demonstrate that pioglitazone treatment did not independently provide any additional clinical benefit to patients with type 2 diabetes admitted with COVID-19 infection.